Pest survey card on Anisogramma anomala. Issue 3 (13th March 2023) - ,; Gionni, Alessandra; Pecori, Francesco; Santini, Alberto; Graziosi, Ignazio; Camilleri, Melanie
Abstract: This document provides the conclusions of the pest survey card that was prepared in the context of the EFSA mandate on plant pest surveillance (M‐2020‐0114) at the request of the European Commission. The full pest survey card for Anisogramma anomala is published and available online in the EFSA Plant Pest Survey Cards Gallery at the following link and will be updated whenever new information becomes available: https://efsa.europa.eu/plants/planthealth/monitoring/surveillance/anisogramma-anomala